Professional Guru PAK dalam Perspektif Etis Teologis Kekristenan - Herkulanus Rangga; Reni Triposa; Marfy Simatauw (ICHTUS: Jurnal Teologi dan Pendidikan Kristiani, 2022)
The expertise and professional skills of the teacher, sir, are a teacher's abilities in the teaching and learning process. teacher professional skills also require expertise that is truly possessed by a professional teacher. In learning Christianity, a teacher's professional competence is also very much needed, especially in today's increasingly developing era. A Christian Religious educator must also have a good personality so that he can be an example for his students as exemplifying Jesus Christ. Not only having a good personality but also having a spirituality that is really owned by a teacher of Christianity. As educators, the Christian religion taught must be Bible-centered, which forms the basis of the material in learning so that what will be delivered is by Bible-centered Christian teachings. The author uses qualitative and descriptive research methods by conducting literature studies on this research. So, the professional competence of teachers in the PAK learning process is the Professional Competence of Teachers in the Learning Process of Christian Religious Education. So the journal is about a teacher's professionalism who must have the ability, skills, and expertise in PAK learning which must be Bible-centered. Abstrak Keahlian dan kecakapan profesional guru pak merupakan kemampuan seorang guru dalam proses belajar mengajar. kecakapan profesional guru juga membutuhkan keahlian yang benar-benar yang dimiliki oleh seorang guru profesional. Proses pembelajaran Agama Kristen kompetensi profesional seorang guru juga sangat dibutuhkan apalagi pada zaman yang semakin berkembang saat ini. Seorang pendidik Agama Kristen juga haruslah memiliki kepribadian yang baik sehingga dapat menjadi teladan bagi para peserta didiknya sebagaimana meneladani Yesus Kristus. Bukan hanya memiliki kepribadian baik saja tetapi spiritualitasnya juga haruslah benar-benar dimiliki oleh seorang pengajar Agama Kristen. Sebagai pendidik Agama Kristen yang diajarkan haruslah berpusat pada Alkitab yang menjadi dasar materi dalam pembelajaran sehingga apa yang akan disampaikan sesuai dengan ajaran Kristen yang berpusat pada Alkitab. Penulis menggunakan metode penelitian kualitatif dan metode deskriptif dengan melakukan studi Pustaka terhadap penelitian ini. Jadi, kecakapan profesional guru dalam proses pembelajaran PAK Kompetensi Profesional Guru dalam Proses Pembelajaran Pendidikan Agama Kristen. Jadi Jurnal tentang seorang profesionalisme guru yang harus memiliki kemampuan, keterampilan, dan keahlian dalam pembelajaran PAK yang harus berpusat pada Alkitab.